2019
DOI: 10.1136/bjophthalmol-2019-313827
|View full text |Cite
|
Sign up to set email alerts
|

Five-year changes in anterior segment parameters in an older population in urban southern China: the Liwan Eye Study

Abstract: PurposeTo investigate the 5-year changes in static and dynamic anterior segment optical coherence tomography (AS-OCT) parameters and their predictors.MethodsThis was a prospective, population-based cohort study of people aged 50 years and older residing in the Liwan District, Guangzhou, China. Standardised AS-OCT scans were performed in November 2008 and November 2013 under dark and light conditions. Customised software was used to analyse horizontal AS-OCT images. Parameters in dark and measurements of light-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Change in angle parameters and in their dynamic change with pupil size is related to subject age. 10 There is now considerable evidence that the dynamic behavior of the iris and choroid are contributing features to PACD. [11][12][13] In all eyes, the iris loses volume by aqueous humor transfer from the iris stroma to the anterior chamber immediately upon pupil dilation.…”
Section: Introductionmentioning
confidence: 99%
“…Change in angle parameters and in their dynamic change with pupil size is related to subject age. 10 There is now considerable evidence that the dynamic behavior of the iris and choroid are contributing features to PACD. [11][12][13] In all eyes, the iris loses volume by aqueous humor transfer from the iris stroma to the anterior chamber immediately upon pupil dilation.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Second, these measurements could be used to track longitudinal progression of angle narrowing or response to treatments for angle closure, such as laser peripheral iridotomy (LPI). [12][13][14][15] Finally, the recent landmark Zhongshan Angle Closure Prevention trial demonstrated that the current definition of primary angle closure suspect, which comprises the vast majority for PACD, may be too broad to guide treatment with LPI. 16 Therefore, AS-OCT measurements, which reflect anatomic and physiologic changes related to angle closure, could complement gonioscopy to refine the management of early stage PACD.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the AL, LT, IT, TCA, and CBT were positively associated with age, while the LV and SFCT were negatively correlated with age. There has been no systematic study that analyzed the relationship between ocular biometric parameters and age in PACD patients, but previous studies of normal populations have shown that the AL,TCA,CBT, and SFCT were negatively correlated with age (12,16,26,27,(30)(31)(32)(33), while the LT, LV, and IT were positively associated with age (12,23). The correlations between age and LT, IT, and SFCT in this study were consistent with those in normal people, but the correlations between age and AL, LV, CBT, and TCA were opposite to those in the normal population.…”
Section: Discussionmentioning
confidence: 99%